Prevalence and risk factors of acute respiratory infection by human respiratory syncytial virus in children at Provincial General Hospital of Bukavu, Democratic Republic of the Congo - Cihambanya, Landry Kabego (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMedSc)--Stellenbosch University, 2017.